Homeownership at any cost : how the National Association of Realtors convinced taxpayers to subsidize the American Dream - Jeffery, Andrew (FT Press Delivers, 2012)
With its extraordinarily powerful Washington lobbying organization, massive political contributions, and members in every Congressional district, the National Association of Realtors (NAR) has distorted U.S. housing policy for generations. NAR's efforts have consistently enriched real estate professionals by making home purchasing artificially cheap and easy. In Homeownership at Any Cost , Andrew Jeffery tells this hidden story, shining a light on NAR's outsized role in designing U.S. housing policies for nearly a century and examining accusations that it played a key role in inflating the housing bubble that nearly destroyed the global financial system. Jeffery recounts the NAR's absurdly rosy projections about real estate markets in the years running up to the mortgage meltdown, showing how the organization has managed to fly "under the radar" while other market players have been pilloried by the media and policy makers. He concludes by revealing the crucial behind-the-scenes role NAR is playing right now in the debate over remaking U.S. housing policy, its self-serving attempts to rewrite federal mortgage policy to suit its own ends, and its advocacy of a near-complete abdication of the mortgage market to the federal government.